Penicillium citrinum UFV1 β-glucosidases: purification, characterization, and application for biomass saccharification - Samara G. da Costa; Olinto Liparini Pereira; André Teixeira-Ferreira; Richard Hemmi Valente; Sebastião T. de Rezende; Valéria M. Guimarães; Fernando Ariel Genta (Biotechnology for Biofuels, 2018)
Abstract Background β-Glucosidases are components of the cellulase system, a family of enzymes that hydrolyze the β-1,4 linkages of cellulose. These proteins have been extensively studied due to the possibility of their use in various biotechnological processes. They have different affinities for substrates (depending on their source) and their activities can be used for saccharification of different types of biomass. In this context, the properties and the synergistic capacity of β-glucosidases from different organisms, to supplement the available commercial cellulase cocktails, need a comprehensive evaluation. Results Two β-glucosidases belonging to GH3 family were secreted by Penicillium citrinum UFV. PcβGlu1 (241 kDa) and PcβGlu2 (95 kDa) presented acidic and thermo-tolerant characteristics. PcβGlu1 showed Michaelis–Menten kinetics for all substrates tested with K m values ranging from 0.09 ± 0.01 (laminarin) to 1.7 ± 0.1 mM (cellobiose, C2) and k cat values ranging from 0.143 ± 0.005 (laminarin) to 8.0 ± 0.2 s−1 (laminaribiose, Lb). PcβGlu2 showed substrate inhibition for 4-methylumbelliferyl-β-d-glucopyranoside (MUβGlu), p-nitrophenyl-β-d-glucopyranoside (pNPβGlu), cellodextrins (C3, C4, and C5), N-octil-β-d-glucopyranoside, and laminaribiose, with K m values ranging from 0.014 ± 0.001 (MUβGlu) to 0.64 ± 0.06 mM (C2) and k cat values ranging from 0.49 ± 0.01 (gentiobiose) to 1.5 ± 0.2 s−1 (C4). Inhibition constants (K i) for PcβGlu2 substrate inhibition ranged from 0.69 ± 0.07 (MUβGlu) to 10 ± 1 mM (Lb). Glucose and cellobiose are competitive inhibitors of PcβGlu1 and PcβGlu2 when pNPβGlu is used as a substrate. For PcβGlu1 inhibition, K i = 1.89 ± 0.08 mM (glucose) and K i = 3.8 ± 0.1 mM (cellobiose); for PcβGlu2, K i = 0.83 ± 0.05 mM (glucose) and K i = 0.95 ± 0.07 mM (cellobiose). The enzymes were tested for saccharification of different biomasses, individually or supplementing a Trichoderma reesei commercial cellulose preparation. PcβGlu2 was able to hydrolyze banana pseudostem and coconut fiber with the same efficiency as the T. reesei cocktail, showing significant synergistic properties with T. reesei enzymes in the hydrolysis of these alternative biomasses. Conclusions The β-glucosidases from P. citrinum UFV1 present different enzymatic properties from each other and might have potential application in several biotechnological processes, such as hydrolysis of different types of biomass.